Between accountability and agency: a comparative analysis of faculty performance evaluation policies in the UAE - Rami Alsharefeen; Mutasim Al-Deaibes (Cogent Education, 2025)
This study interrogates faculty performance evaluation policies across UAE higher-education institutions using Saunders’ RUFDATA and Priestley’s educator-agency frameworks. RUFDATA proved a robust meta-evaluative lens, revealing that most policies align with established best practice: they articulate explicit purposes (faculty development, merit pay, academic excellence), specify uses (diagnosing improvement areas, fostering collegiality, informing promotion and contract renewal), embed faculty in goal-setting, and impose clear timelines. Nonetheless, notable deficiencies persist. Policies rarely stipulate aspirational targets, permit staff to identify requisite resources, or address the complexities of cross-departmental appointments, thereby constraining evaluative equity. Policy orientation is further shaped by institutional age and affiliation. Concerning agency, discourse varies: while dialogic goal formulation and mid-cycle reviews are generally encouraged, opportunities for faculty to register dependencies and resource needs are limited, circumscribing their practical autonomy. Overall, UAE institutions have embraced many contemporary recommendations, yet must widen provisions that enable staff to negotiate goals and secure support, especially where responsibilities traverse departmental boundaries. Enhancing these dimensions would strengthen educator agency and, by extension, the developmental and organisational value of evaluation systems.